BLOOD PRESSURE AMBULATORY MONITORING AS A METHOD FOR EARLY HYPERTENSION DIAGNOSTICS IN RHEUMATOID ARTHRITIS PATIENTS - N. M. Nikitina (Российский кардиологический журнал, 2017)
Aim. To study the specifics of arterial hypertension (AH) taking the data from ambulatory monitoring (ABPM) in rheumatoid arthritis patients (RA).Material and methods. Totally, 105 women with RA included (mean age — 55,49±7,02 y. o., mean age of RA onset — 45,17±10,87 y. o., mean duration of RA — 10,79±10,01 y., activeness by DAS28 — 5±1,14). By the data from office BP, 2 groups were selected: first group — 56 patients with RA and AH (RA+AH), second group — 49 patients with RA, non-AH. Exclusion criteria were smoking, diabetes, secondary AH, associated clinical conditions of AH, exacerbated chronic conditions, pregnancy, lactation, malignancies. Comparison group included 30 females with essencial AH, non-RA and other inflammatory disorders of the joints and spine (mean age — 55,9±6,2 y. o.), controls consisted of 22 almost healthy volunteers (females, mean age — 54,13±6,25 y. o.). Patients underwent ABPM, laboratory investigations with total cholesterol, creatinine, C-reactive protein (hsCRP), ESR. The glomerular filtration rate (GFR) was calculated by CKD-EPI, activeness of RA by DAS28.Results. In general AH was found in 64,7% of RA patients, 11,4% were not aware of it, 57,3% did not control BP, and just 9,0% took 3-component antihypertension treatment. By ABPM, masked AH was found in 33,3% patients RA non-AH. Traditional risk factors in RA patients with essential and masked hypertension had same prevalence. By the ABPM data, RA hypertensives had worse nocturnal SBP profile comparing to AH and controls (p<0,05). More than a half of RA patients had high BP variability, in RA patients there was more prevalent BP raising at night (nightpeakers). The relation was found, of nocturnal SBP and HS-CRP (r=0,36, р<0,05), ESR (r=0,64, р<0,05).Conclusion. AH in RA patients is more prevalent than in general population (53,3% by office BP, and 64,7% taking ABPM) The problem of AH screening in RA patients is important, and ABPM is recommended for earlier assessment.